PENGARUH TRANSPORTASI JARAK PENDEK TERHADAP PERUBAHAN GAMBARAN TOTAL DAN DIFERENSIAL LEUKOSIT KAMBING PERANAKAN ETTAWA (Caprae hircus) DI KULON PROGO - , MUJI LESTARI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The routine transportation of cross-bred ettawa does between farm and market or other cities for slaughtering has been running almost everyday. The length of time of transportation is various. There it can start short distance or long distance. The aim of research to know the effects of one hour toward of changing leukocytes and differential leukocytes such as basophils, eosinophils, limphocyts, monocyte and neutrophils in cross-bred ettawa das. All animals were transportation in pick up truck from Girimulyo to Nanggulan (Â± 35 km) within one hour. Blood sample was drawn from jugular vein about 3 ml, at the time before transportation, after transportation, and seven days after transportation. The blood sample was used for leukocytes examination. The result showed that count of leucocyte and differential leucocytes before transportation, after transportation and sevent days after transportation 797 cells/mm3, 8833,3 cells/mm3, and 8308 cells/mm3, segmented neutrophils 3276,66 cells/mm3, 4520,1 cells/mm3, 3178,67 cell/mm3